Interspersion of sequences in avian myeloblastosis virus rna that rapidly hybridize with leukemic chicken cell DNA. - Drohan, W N (1975)
Liquid hybridization of progressively smaller fragments (35S, 27S, 15.5S, 12.5S, and 8S) of poly(A)-selected avian myeloblastosis virus RNA with excess DNA from leukemic chicken myeloblasts revealed that all sizes of RNA contained sequences complementary to both slowly and rapidly hybridizing cellular DNA sequences. Apparently, the RNA sequences which hybridize rapidly with excesses of cellular DNA are not restricted to any one region of the avian myeloblastosis virus 35S RNA. Instead, they appear to be randomly distributed over the entire 35S avian myeloblastosis virus RNA molecule with some positioned within 200 nucleotides of the poly(A) tract at the 3' end of the RNA.